The Use of Integrated Crop–Livestock Systems as a Strategy to Improve Soil Organic Matter in the Brazilian Cerrado - Stallone Soares; Wesley Souza; Bruno Homem; Israel Ramalho; João Borré; Marcos Pereira; Érika Pinheiro; Robelio Marchao; Bruno Alves; Robert Boddey; Segundo Urquiaga (Agronomy)
This study aimed to analyze the carbon (C) stock and stabilization of soil organic matter in particulate- and mineral-associated fractions across different land use systems after 32 years of experimentation in the Brazilian Cerrado. The experiment was established in 1991 and was performed in Planaltina-DF. The treatments evaluated included continuous pasture with monoculture grasses; integrated crop–livestock systems under no tillage; continuous cropping under no tillage; minimum tillage; and the preservation of the native Cerrado biome in its original condition. Soil sampling was performed to a depth of 30 cm. Carbon and nitrogen (N) stocks were quantified for the years 2001, 2009, 2013, and 2023, with soil organic matter fractionation performed on samples from 2023. Land use change resulted in significant losses of soil C and N in areas managed with conventional soil preparation practices. Systems that promote plant diversity, such as integrated crop–livestock systems, enhanced soil C and N stocks (72.8 and 5.5 Mg ha−1, respectively) and increased both particulate organic matter and mineral-associated fractions, most of which were in more stabilized forms. Integrated crop–livestock systems are management practices that offer an effective alternative to present methods in terms of combating climate change and supporting ecosystem sustainability.